Biosynthesis of silver nanoparticles efficacy against selected human pathogens - MASESE OSORO BRIAN; S. SELVI (International Journal of Pharma and Bio Sciences, 2019)
The aim of the present study is to investigate the synthesis and characterization of silver nanoparticles (AgNPs), and their antibacterial effect on gram positive and gram negative bacteria human pathogens by using ethanolic bark extract of Ceiba pentandra. Silver nanoparticleswere prepared by green synthesis process using Silver Nitrate. When exposed to the ethanolic bark extract of Ceiba pentandra, the aqueous silver ions were reduced and stabilized over long periods of time resulting in the green synthesis of surface functionalized silver nanoparticles. The bio-reduced Silver nanoparticles were synthesized and characterized by UV-visible spectroscopic analysis, XRD, TEM, FTIR analysis. The synthesized AgNPs antimicrobial activity was evaluated on both gram positive and gram negative bacteria by agar well diffusion method. Ciprofloxacin was used as standard antibiotic drug. The aqueous Silver Nitrate solution changed from pale yellow to reddish brown color after incubation. UV-visible spectroscopic analysis showed the absorbance peak at around 450 nm which indicates the synthesis of Ag NPs. TEM image showed the formation of well-dispersed silver nanoparticles in the range of 5-25 nm. X-ray diffraction (XRD)-spectrum as evidenced by the peaks at 2θ values of such peaks 38.43°, 44.40°, and 67.57°, corresponds to 111, 200 and 220 planes for silver, respectively. Silver nanoparticles showed the antibacterial activity against Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli bacterium. This study demonstrated that the silver nanoparticles from Ceiba pentandra bark extract are more stable and have a remarkable antibacterial activity against human pathogens.